Pengenalan Permainan Tradisional Jawa, Sunda, Batak dan Cina untuk Tingkat Sekolah Dasar - Sentia Rahmadani; Muhammad Zidan Abdillah; Nur Hayati Oktavia; Budiana Budiana (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2019)
PKM-M activity about Introduction of tradisional game from Java, Sundanese, Batak and Chinese at SDN 005 Batam Kota. This Activity involved PKM-M team and the volunters from HME, KUAS and from social society with non profit. Th activity about Introduction of traditional game was done with using some methods such as pra-community service, community service and after community service. The purpose of this activity is to introduction traditional game In Indonesia especially traditional game like Margalah from Batak, Cing Ciripit from Sundanese, Lulu Cina Buta from Malay, Gasing from Javanese and Yoyo China from Chinese. The Implementation methode from this community services was used by theory methode and practical methode. The result of PKM-M is the student from 5C class in SDN 005 Batam Kota knowing about traditional game such as Margalah, Cing ciripit, Lulu Cina Buta, Gasing and Yoyo China.